Chemical show in Atlantic City, New Jersey (1954) - Hercules Incorporated (1954)
General view of a portion of the Hercules Powder Company display exhibited at a 1954 trade show held at Chalfonte-Haddon Hall in Atlantic City, New Jersey. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Advertising; Advertising, Industrial; Chemical industry; Corporations; Hercules Incorporated; Trade shows